PELAKSANAAN PROGRAM SEKOLAH BERWAWASAN GENDER DI PROPINSI RIAU - Yenita Roza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Gender mainstreaming being the big issues lately included in Indonesia. To improve the gender equality access for education Indonesian government been launching the schools program name “ Sekolah Berwawasan Gender”. The aim of this study is to explore the schools’ achievement on that government program in The Province of Riau. Giving orientation program, schools were required to design and implement their specific program. Schools also get funded to accelerate their program. The assessment were done based on 10 standard on indicator of the program implementation. Data were collected through questionnaire and direct observation to the schools. This paper discuss finding based on the 10 standard that grouped into schools level and region of the schools. It was found that the highest achievement is reached for standard 3 (85%) that deal with learning outcome, the lowest achievement is given to the standard 5 (56%) about schools’ facilities. This finding will be used as recommendation for the schools and government to improve their program design and implementation of gender equality program.